Assessment of the Effect of Anticipated Factors on Real Estate Investment Performance of Insurance Companies in Nigeria - Inuwa Mohammed Danlami; Zairul Nisham Musa (International Journal of Property Sciences (E-ISSN: 2229-8568), 2025)
Nigeria has a severe housing shortage of almost 28 million units, which is impeding social stability and economic prosperity. The National Housing Fund (NHF) Act and other legislative frameworks require insurance companies to invest a percentage of their premiums in real estate; nonetheless, the sector’s actual investment is still quite small. To determine and rank the internal and external factors influencing Nigerian insurance firms’ success in real estate investments, this study combines Factor Analysis, Principal Component Analysis (PCA), and the Relative Importance Index (RII) in a novel way. Structured questionnaires were used to collect data from 44 insurance companies, yielding solid, industry-specific insights. A methodological strength that improves the efficiency and clarity of interpretation is the PCA’s ability to reduce 24 variables to six essential components, which together account for 83.32% of the total variance. While external variables like infrastructure, governance, and investor perception were shown to be significant but less dominant, internal factors like capital volume and fixed assets had the strongest influence (RII > 0.87). The study provides a new, empirically supported paradigm for identifying investment obstacles by fusing RII and PCA. By addressing the discrepancy between policy expectations and actual investment behaviours, this study contributes to the body of knowledge by providing specific recommendations for infrastructure planning, institutional capacity building, and policy reinforcement. The results offer a calculated plan for employing insurance cash to alleviate the housing situation in Nigeria.